The Effect of Irrigation System and Crop Load on the Vigour of Barlinka Table Grapes on a Sandy Soil, Hex River Valley - Saayman, D.; Lambrechts, J.J.N. (South African Journal of Enology and Viticulture, 2017)
The effect of drip and micro-sprinkler irrigation, as well as crop load, on the vigour of Barlinka table grapes was studied in a field trial in the Hex River Valley over a 12-year period. Regulating soil water by means of tensiometers alone proved to be ineffective in the case of drippers, causing reduced vigour compared to micro-sprinklers. This could be rectified by using a fixed 2-day schedule and evaporation data. Increased bunch numbers per vine were found to have a pronounced and consistently depressive effect on shoot mass. It was proposed that an approach be followed of deciding on an acceptable vigour and then allocating bunches accordingly, using a formula developed from data obtained in this experiment. Significant seasonal variation in vigour caused by crop load and indications of similar effects due to calculated water deficits, were obtained. Combining these two factors in a regression model, shoot mass data were recalculated, revealing no consistent effect of irrigation systems on shoot growth. Mean seasonal water requirements were found to be 569 mm for micro-sprinklers and 411 mm for drippers. The more than 25% saving with drippers was mainly due to a reduced wetted soil volume.